GREEN INFRASTRUCTURE NETWORK (GIN) SOLUTIONS FOR A CONDUCIVE STREET NETWORK AT LOW-COST HOUSING AND THE NEIGHBOURHOOD OF UKAY PERDANA, ULU KLANG, SELANGOR - Alambuaina, Iffah Fadhilah; Mansor, Mazlina; Ibrahim, Putri Haryati; Md Jani, Haza Hanurhaza (Journal of Architecture, Planning and Construction Management, 2023)
Urban green infrastructure includes the street network a green amenity for people. It comprises transportation corridors, a linear pedestrian network, and linear green areas and reserves. The streets serve as a vital network connecting various facilities in a housing area. Applying a green infrastructure network (GIN) will contribute significantly to housing areas, particularly in low- and middle-income communities. It can facilitate people's access to various locations in and around the neighbourhood, thereby fostering a healthy society. The paper analyses the conditions of the green infrastructure network (GIN) in the form of the street network of Jalan Ukay Perdana at Sri Impian Flat and its neighbourhood of Ukay Perdana. The street network selected for the study is within 500 metres of the flat and the surrounding neighbourhood. In addition to a literature review, the study employed spatial mapping, analysis, and site observation. The methods were utilised to identify and assess the streets as pedestrian and transportation networks within the neighbourhood. The existing elements and potential GIN were examined to give recommendations for GIN solutions for street networks in the housing area. The proposal is suggested to promote the local community's well-being in low-cost housing areas. Keywords: Green infrastructure, green network, street, pedestrian connectivity, affordable housing